Research partnerships across international contexts: a practice of unity or plurality?. Issue 5 (4th July 2022) - Perry, Mia; Sharp, Jo; Aanyu, Kevin; Robinson, Jude; Duclos, Vanessa; Ferdous, Raihana
ABSTRACT: Partnership is not a benign practice; it is culturally and ethically loaded. The way in which partnerships are construed in international research determines its design, ethics and impacts. Despite this, and the growing assumption of partnership practice in our field, the concept has become increasingly abstract and the practice under-analysed. This article provides critical perspectives of current understandings of partnership in international development research from three angles: the motivations behind partnership working; an epistemological perspective in relation to epistemic justice and the agency of language; and finally, the systems that mediate partnerships, and the range of resources that guide them.